2008
DOI: 10.1017/s0022112008001353
|View full text |Cite
|
Sign up to set email alerts
|

High concentrations of a passive scalar in turbulent dispersion

Abstract: In problems involving the dispersion of hazardous gases in the atmosphere, the distribution of high concentrations is often of particular interest. We address the modelling of the distribution of high concentrations of a dispersing passive scalar at large Péclet number, concentrating on the case of steady releases. We argue, from the physical character of the small-scale processes, and from the statistical theory of extreme values, that the high concentrations can be fitted well by a Generalized Pareto Distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
3

Year Published

2008
2008
2011
2011

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 40 publications
3
27
3
Order By: Relevance
“…The simple relationship (7) resulting from the single concentration level model has been generalized (Mole and Clarke 1995;Schopflocher and Sullivan 2005;Mole et al 2008) to…”
Section: An Exact Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The simple relationship (7) resulting from the single concentration level model has been generalized (Mole and Clarke 1995;Schopflocher and Sullivan 2005;Mole et al 2008) to…”
Section: An Exact Resultsmentioning
confidence: 99%
“…For the idealized "two-level" model for the release, where the concentration is either zero or C m , the effects of molecular diffusivity are particularly important (Zimmerman and Chatwin 1995;Mole et al 2008). The skewness (4) attains negative values in the case λ 2 − λ 2 2 − 8λ 3 λ 1 /9 < (4/3) λ 2 1 α < λ 2 + λ 2 2 − 8λ 3 λ 1 /9, with λ 2 2 ≥ 8λ 3 λ 1 /9, while also (a) (b) Fig.…”
Section: Continuum Modelmentioning
confidence: 99%
“…Consequently, both c rms−max /c max and measures of the relative extreme concentrations (i.e. maximum possible concentration normalised by the mean, Xie et al, 2007;Mole et al, 2008) are expected to be lower for line than for point sources.…”
Section: Concentration Fluctuationmentioning
confidence: 99%
“…3. Mole et al (2008) provide a discussion of the widely observed representation of a substantial range of the highest concentration values by a generalized Pareto density function. They observed that there was little variation of the parameters, including the maximum concentration, over a plume cross-section.…”
Section: Introductionmentioning
confidence: 99%